Establishment of Reference Interval for M2BPGI Glyco-Biomarker in the Serum of Mongolian People - Enkhbayar, Uranbaigali; Khuyagaa, Ser-Od; Dambadarjaa, Davaalkham; Namdag, Bira; Radnaa, Otgonbayar (Central Asian Journal of Medical Sciences, 2020)
Objectives: Establishment of reference interval for M2BPGI glyco-biomarker in the serum of relatively healthy Mongolian people. Methods: Serum analysis for M2BPGI glyco-biomarker, hepatitis virus markers, and AFP analysis were performed using a fully automated chemiluminescence immunoassay analyzer. Non-parametric methods were used for establishment of reference interval according to the guideline of the Clinical Laboratory Standards Institute. Statistical analysis was done by using SPSS ver. 20.0; SPSS Inc., Chicago, IL software. Results: Total of 3384 people were involved in this study. Of the total participants, 40% were overweight and 31.3% were obese. Also, of the population 10.1 percent were positive for HBsAg, 17 percent were positive for Anti-HCV, and 1.1 percent had co infection of both HBV and HCV. A total of the 316 individuals met the inclusion criteria for reference interval establishment and 77 (24.4%) of them were men and 239 (75.6%) were women. The reference interval of M2BPGI glyco-biomarker for men was 0.883 ± 0.311C.O.I and for women was 0.951 ± 0.411C.O.I. Conclusion: It is determined that the reference interval for M2BPGI glyco-biomarker in the serum of relatively healthy Mongolian people was 0.936 ± 0.391C.O.I.